Paternal easiRNAs regulate parental genome dosage in Arabidopsis. (February 2018) - Martinez, German; Wolff, Philip; Wang, Zhenxing; Moreno-Romero, Jordi; Santos-González, Juan; Conze, Lei; DeFraia, Christopher; Slotkin, R.; Köhler, Claudia
Abstract The regulation of parental genome dosage is of fundamental importance in animals and plants, as exemplified by X-chromosome inactivation and dosage compensation. The 'triploid block' is a classic example of dosage regulation in plants that establishes a reproductive barrier between species differing in chromosome number1, 2 . This barrier acts in the embryo-nourishing endosperm tissue and induces the abortion of hybrid seeds through a yet unknown mechanism3 . Here we show that depletion of paternal epigenetically activated small interfering RNAs (easiRNAs) bypasses the triploid block in response to increased paternal ploidy inArabidopsis thaliana . Paternal loss of the plant-specific RNA polymerase IV suppressed easiRNA formation and rescued triploid seeds by restoring small-RNA-directed DNA methylation at transposable elements (TEs), correlating with reduced expression of paternally expressed imprinted genes (PEGs). Our data suggest that easiRNAs form a quantitative signal for paternal chromosome number and that their balanced dosage is required for post-fertilization genome stability and seed viability. Depletion of easiRNAs (epigenetically activated small interfering RNAs) relieves the triploid block reproduction barrier mediated by increased paternal ploidy inArabidposis . Loss of RNA Pol IV blocks easiRNA formation and rescues triploid seeds.